THE IMPACT OF CLEANER AND LEAN PRODUCTION ON SUSTAINABILITY: A COMPARATIVE STUDY BETWEEN A GROUP OF INDUSTRIAL COMPANIES IN BASRA GOVERNORATE - Safaa Mohammed Hadi Hashim; Hind Salim Abood (Galaxy International Interdisciplinary Research Journal, 2023)
The study aims to identify the extent to which industrial companies contribute to adopting cleaner production strategies in terms of practice and level of performance as a precautionary approach by seeking to reduce environmental waste, as well as the contributions of those companies to waste disposal in the production chain to reduce costs and improve quality and delivery time through Its applied adoption of lean production practices, and the problem of the study revolves around several fundamental questions, most notably the extent to which industrial companies apply lean production and does this lead to cleaner production? The importance of the study is represented in the field dimension based on attempts to diagnose and analyze the reality of the thirteen companies studied and to identify areas of benefit from the nature and importance of the existing relationship between the variables of the study (lean manufacturing, cleaner production, sustainability) in reducing the risks of production activities, reducing the environmental impact and making the companies’ operations More sustainable The study reached several conclusions, the most important of which is that there is a relationship between the two systems of lean manufacturing and cleaner production, as lean manufacturing practices contribute to achieving cleaner production, which causes less impact on the environment.